Cytotoxic and inflammatory potential of a phospholipase A2 from Bothrops jararaca snake venom Suely V. Sampaio, Eliane C. Arantes, Marco A. Sartim - Cedro, Rafhaella C. A.; Menaldo, Danilo L.; Costa, Tássia R.; Zoccal, Karina F.; Sartim, Marco A.; Santos-Filho, Norival A. [UNESP]; Faccioli, Lúcia H.; Sampaio, Suely V. (Springer Nature, 2018)
Background: Snake venom phospholipases A2 (PLA2s) have been reported to induce myotoxic, neurotoxic, hemolytic, edematogenic, cytotoxic and proinflammatory effects. This work aimed at the isolation and functional characterization of a PLA2 isolated from Bothrops jararaca venom, named BJ-PLA2-I. Methods and Results: For its purification, three consecutive chromatographic steps were used (Sephacryl S-200, Source 15Q and Mono Q 5/50 GL). BJ-PLA2-I showed acidic characteristics, with pI~ 4.4 and molecular mass of 14.2 kDa. Sequencing resulted in 60 amino acid residues that showed high similarity to other Bothrops PLA2s, including 100% identity with BJ-PLA2, an Asp49 PLA2 previously isolated from B. jararaca venom. Being an Asp49 PLA2, BJ-PLA2-I showed high catalytic activity, and also inhibitory effects on the ADP-induced platelet aggregation. Its inflammatory characterization showed that BJ-PLA2-I was able to promote leukocyte migration in mice at different concentrations (5, 10 and 20 μg/mL) and also at different response periods (2, 4 and 24 h), mainly by stimulating neutrophil infiltration. Furthermore, increased levels of total proteins, IL-6, IL-1β and PGE2 were observed in the inflammatory exudate induced by BJ-PLA2-I, while nitric oxide, TNF-α, IL-10 and LTB4 levels were not significantly altered. This toxin was also evaluated for its cytotoxic potential on normal (PBMC) and tumor cell lines (HL-60 and HepG2). Overall, BJ-PLA2-I (2.5-160 μg/mL) promoted low cytotoxicity, with cell viabilities mostly varying between 70 and 80% and significant values obtained for HL-60 and PBMC only at the highest concentrations of the toxin evaluated. Conclusions: BJ-PLA2-I was characterized as an acidic Asp49 PLA2 that induces acute local inflammation and low cytotoxicity. These results should contribute to elucidate the action mechanisms of snake venom PLA2s.
Keywords: Bothrops jararaca; Cytotoxicity; Inflammation; Phospholipase A2; Snake venom